Therapeutic with aquascape / Farhan Faat and Nik Mohd Shahril Nik Mohd Nor - Faat, Farhan; Nik Mohd Nor, Nik Mohd Shahril (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Have you ever wonder why some clinics and hospital display fish tanks in surgeries and dental waiting rooms? Have you ever heard about aquascape? And do you know that this unique aquarium system could promote a good health. Well, in 2015 a study by Deborah Cracknell, Dr Sabine Pahl and Dr Matthew White from The National Marine Aquarium, University of Plymouth & University of Exeter found that people who spend time sitting and watching fish in an aquarium can improve their physical and mental well-being. The more fish they watched and the longer time spent viewing underwater nature eventually helps improves their mood. Dr Sabine Pahl also mentioned that "In times of higher work stress and crowded urban living, perhaps aquariums can step in and provide an oasis of calm and relaxation". This provides evident that doses of exposure to underwater settings could actually have a positive impact on people's wellbeing. Specifically, it shows that spending time in a natural environment such as underwater has a therapeutic effect on human. It helps the blood pressure and heart rate lowered whilst viewing the aquarium.